An Exploratory Analysis of the Association Between Hospital Labor Costs and the Quality of Care - Beauvais B; Kruse CS; Ramamonjiarivelo Z; Pradhan R; Sen K; Fulton L (Dove Medical Press, 2023)
Brad Beauvais,1 Clemens Scott Kruse,1 Zo Ramamonjiarivelo,1 Rohit Pradhan,1 Keya Sen,1 Lawrence Fulton2 1School of Health Administration, Texas State University, San Marcos, TX, USA; 2Woods College of Advancing Studies, Boston College, Chestnut Hill, MA, USACorrespondence: Brad Beauvais, School of Health Administration, Texas State University, San Marcos, TX, USA, Email bmb230@txstate.eduIntroduction: The competent healing touch of a caregiver is a critical component to the care patients receive. The more skilled the provider, the higher the likelihood outcomes will be delivered in a safe and effective manner. Unfortunately, in recent years, hospitals in the United States have faced immense financial pressures that are threatening their economic sustainability and patients' access to care in the future. Through the recent COVID-19 pandemic, the cost of delivering healthcare has continued to escalate, while the demand for patient care has exceeded many hospitals' capacity. Most troubling is the impact that the pandemic has had on the healthcare workforce, which has resulted in many hospitals struggling to fill vacancies at ever-increasing cost - all while under immense pressure to deliver quality patient care. What remains uncertain is whether the increase in labor costs has been matched with a commensurate rise in the quality of care or if quality has deteriorated as the labor force mix has changed to include more contract and temporary staff. Thus, in the enclosed study, we sought to determine what association, if any, exists between hospitals' cost of labor and the quality of care delivered.Methods and Models: Drawing from a representative national sample of nearly 3214 short-term acute care hospitals' common quality measures from the year 2021, we examined the labor cost-quality relationship via multivariate linear and logistic regression and found there is a persistent negative association across all quality outcome variables studied.Discussion: These findings lead us to believe simply paying more for hospital labor does not, by itself, ensure a positive patient outcome. We contend cautious use of temporary staff, measured adoption of short-term financial incentives, and robust staff development all should be considered as features of future workforce planning.Keywords: hospital, labor costs, quality